Intensive critical care nurses' with limited experience: Experiences of caring for an organ donor during the donation process. Issue 9 (7th February 2020) - Simonsson, Johan; Keijzer, Karl; Södereld, Theres; Forsberg, Angelica
Abstract: Objective: To describe how intensive critical care nurses, whose experience is limited, experience caring for an organ donor during the donation process. Background: Intensive critical care nurses are involved in the care of organ donors and their relatives. This may be challenging and evoke a sense of providing an inhumane care. Few studies have explored how intensive critical care nurses whose experience is limited experience caring for an organ donor during the donation process. Design: An interview study with an inductive qualitative approach was conducted. The study was reported according to COREQ guidelines. Methods: This study was performed during 2019. Participants were intensive critical care nurses ( n  = 7) from different hospitals ( n  = 4) with <3 years of experience and involvement in the donation process at least once but no more than three times. Data were analysed using qualitative content analysis. Findings: Five categories emerged: the donation process is emotionally challenging; supporting relatives is an essential but demanding task; a complex and multifaceted process involving a high level of responsibility; needing appropriate prerequisites in the form of education and collegial support; and providing a dignified care based on respect for the organ donor. Conclusions: Having limited experience as an intensive critical care nurse may not automatically mean that caring for an organ donor is experienced as more challenging than it is for a more‐experienced colleague. However, certain intensive critical care nurses whose experience caring for an organ donor is limited found it to be highly demanding due to its complexity, specifically in regard to informing relatives of the loss of their loved one and providing them with support. Relevance to clinical practice: Our study revealed a need for further education. This need could be met by simulation tasks during the specialist education in intensive critical care nursing, where primarily ethical aspects and strategies for meeting with and supporting relatives should be examined and practiced.